Out-of-hospital cardiac arrest in patients with psychiatric disorders — Characteristics and outcomes. (October 2019) - Barcella, Carlo Alberto; Mohr, Grimur H.; Kragholm, Kristian; Blanche, Paul; Gerds, Thomas A.; Wissenberg, Mads; Hansen, Steen M.; Bundgaard, Kristian; Lippert, Freddy K.; Folke, Fredrik; Torp-Pedersen, Christian; Kessing, Lars V.; et al.
Abstract: Aims: To investigate whether the recent improvements in pre-hospital cardiac arrest-management and survival following out-of-hospital cardiac arrest (OHCA) also apply to OHCA patients with psychiatric disorders. Methods: We identified all adult Danish patients with OHCA of presumed cardiac cause, 2001–2015. Psychiatric disorders were defined by hospital diagnoses up to 10 years before OHCA and analyzed as one group as well as divided into five subgroups (schizophrenia-spectrum disorders, bipolar disorder, depression, substance-induced mental disorders, other psychiatric disorders). Association between psychiatric disorders and pre-hospital OHCA-characteristics and 30-day survival were assessed by multiple logistic regression. Results: Of 27, 523 OHCA-patients, 4772 (17.3%) had a psychiatric diagnosis. Patients with psychiatric disorders had lower odds of 30-day survival (0.37 95% confidence interval 0.32–0.43) compared with other OHCA-patients. Likewise, they had lower odds of witnessed status (0.75 CI 0.70–0.80), bystander cardiopulmonary resuscitation (CPR) (0.77 CI 0.72–0.83), shockable heart rhythm (0.37 95% CI, 0.33–0.40), and return of spontaneous circulation (ROSC) at hospital arrival (0.66 CI 0.59–0.72). Similar results were seen in all five psychiatric subgroups. The difference in 30-day survival between patients with and without psychiatric disorders increased in recent years: from 8.4% (CI 7.0–10.0%) in 2006 to 13.9% (CI 12.4–15.4%) in 2015 and from 7.0% (4.3–10.8%) in 2006 to 7.0% (CI 4.5–9.7%) in 2015, respectively. Conclusion: Patients with psychiatric disorders have lower survival following OHCA compared to non-psychiatric patients and the gap between the two groups has widened over time.